Investigating the Mediating Role of Identity Styles on Body Image Concerns and Related Factors in Adolescents Referred to Zahedan Health Centers - Mahvash Raghibi; Haneye Sheikh; Yaser Shamsollahzadeh; Morteza Jalmbadani (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Adolescence is associated with physical, psychological, cognitive, emotional, and social changes in a person's life. During this time, the concepts of identity and body image are raised, both of which can lead to anxiety and ultimately social avoidance. In this regard, the present study was conducted to investigate the mediating role of identity styles in body image and social avoidance of adolescents referred to health centers in Zahedan, Iran, in 2018-2019. Methods: The present descriptive-correlational (correlational-predictive) study was performed on 128 adolescents referred to healthcare centers. The sampling was conducted using the convenience sampling method, and data collection tools were the questionnaires of body image concerns, social avoidance and distress, as well as identity styles. Data analysis performed by SPSS software (version 16) using descriptive statistics, Pearson correlation coefficient, as well as stepwise and standard regressions. Results: Results of the present study indicated that identity styles, including diffuse-avoidant, normative, and commitment, were able to predict and determine variations related to body image concerns (P<0.01). Moreover, the normative identity style could predict and determine variations associated with social avoidance and distress (P<0.01). Furthermore, the results indicated that body image concerns could predict and determine the variations related to social avoidance and distress (P<0.05). Conclusion: Identity styles and body image during adolescence can weaken communication skills, have adverse effects on the levels of adolescents' social interactions with others, and deprive them of having the opportunity to acquire mental, physical, and social skills. Therefore, the risks associated with the aforementioned issues should be taken into consideration, and culture should be extensively developed in national and transnational levels in this regard.